Effects of soft tissue surgery on transverse kinematics in patients with cerebral palsy - Park, Byeong-Seop (BMC Musculoskelet Disord, 2019)
BACKGROUND: Gait disturbances, including flexed knee gait, stiff knee gait, and tip-toeing gait, are common in patients with cerebral palsy (CP). There has been no reports regarding kinematic changes in the transverse plane after soft tissue surgeries, such as distal hamstring lengthening (DHL), rectus femoris transfer (RFT), and tendo-Achilles lengthening (TAL). This study aimed to evaluate changes in the transverse plane after soft tissue surgery in patients with CP by assessing the effects of the DHL, RFT, and TAL. METHODS: The study enrolled 156 consecutive patients (mean age, 8.4 years; range, 4.4 to 20.9), representing 213 operated limbs, who underwent soft tissue surgery including DHL with semitendinosus transfer, RFT, and TAL. All patients were assessed by preoperative and 1-year postoperative three-dimensional gait analysis. Changes in transverse plane kinematics after soft tissue surgery and affecting factors were analyzed. RESULTS: Sagittal kinematics including knee flexion at initial contact, ankle dorsiflexion at initial contact, and mean ankle dorsiflexion in the stance phase were significantly improved after single event multilevel surgery (all p < 0.001). Transverse kinematics, including mean tibial rotation and foot progression angle, were significantly improved to a more external angle after soft tissue surgeries (− 2.9°, p = 0.004 and − 9.5°, p < 0.001). The mean hip rotation was significantly improved to a more external angle by RFT (− 4.7°, p = 0.010) and the foot progression angle was significantly improved to a more external angle by TAL (− 3.9°, p = 0.028). CONCLUSIONS: This study found that the transverse kinematics were improved to a more external angle after soft tissue surgery in patients with CP. Therefore, clinicians should consider that soft tissue surgery can affect the transverse plane kinematics in patients with CP. To confirm our findings, further research regarding the natural history of femoral and tibial torsion in children with CP is needed.